Status Hukum Rekomendasi DP3A dalam Pembebasan Pernikahan Anak: Perspektif Maqāṣid Al-Sharīʿah dan Qawāʿid Fiqhiyyah di Kabupaten Bone - Mustafa, Mustafa; Jumarni, Jumarni (Pascasarjana UIN ANTASARI Banjarmasin, 2025)
The high rate of child marriage dispensation cases in Bone Regency underscores the urgency of strengthening child protection within the framework of Islamic family law. In this context, the recommendations issued by the Department of Women’s Empowerment and Child Protection (DP3A) have become a crucial component in judicial considerations at the Religious Court, despite ongoing debates about their legal status. This study investigates the legal standing of DP3A’s recommendations in child marriage dispensation cases using an Islamic legal approach grounded in qawāʿid fiqhiyyah and maqāṣid al-sharīʿah. A qualitative method was employed, with fieldwork conducted at the DP3A office and the Watampone Religious Court. Data were collected through observation, documentation, and in-depth interviews, and analyzed using descriptive qualitative techniques. The findings reveal two key points: first, DP3A’s recommendations are based on government policy aimed at preventing child marriage and are designed to protect four key aspects of maqāṣid al-sharīʿah: the preservation of life (ḥifẓ al-nafs), intellect (ḥifẓ al-ʿaql), wealth (ḥifẓ al-māl), and dignity (ḥifẓ al-ʿirḍ) of the child. Second, although not formally binding by law, the recommendations are treated as mandatory for marriage dispensation applicants at the Watampone Religious Court and are aligned with Islamic legal principles through the lens of qawāʿid fiqhiyyah and maqāṣid al-sharīʿah. These recommendations reflect a constructive synergy between regional policy and Islamic law in promoting child protection. This study contributes to the advancement of contemporary Islamic legal thought and supports the development of local regulations that are more responsive and grounded in public interest (maṣlaḥah).